Analysis of The Effectiveness of the BukuWarung Application as a Financial Management Tool for MSMEs - Tarissa Aqilla Rahmah; Fajar Syaiful Akbar (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Effective financial management is crucial for business success, especially amid the Industry 5.0 revolution, which has transformed production, management, and human-machine interactions. This era has introduced advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), robotics, and additive manufacturing into production environments, leading to significant changes in accounting practices. In Indonesia, SMEs, traditionally reliant on manual record-keeping, are encouraged to adopt digital applications to remain current. Consequently, various financial management applications have emerged, including BukuWarung, designed to streamline transaction recording and enhance financial management efficiency. This research aims to assess the effectiveness of BukuWarung as a financial management tool for SMEs. Utilizing a qualitative and descriptive approach, the study involved SMEs at SWK Lidah Wetan that use BukuWarung. Primary data were gathered through observation, interviews, and field documentation. Findings reveal that BukuWarung significantly aids SME financial management, particularly in billing, bookkeeping, cashier operations, inventory management, and transaction scheduling. Future research should explore the utilization of specific features within BukuWarung and their effects on SME financial management.